‘I will achieve everything on my own’: the association between early psychosocial skills and educational progression through adolescence in India - Singh, R; Kesarwani, R; Mukherjee, P (Young Lives, 2018)
Psychosocial skills are an important element of the confidence and motivation to progress in academic life. This working paper utilises a factorial logistics model to highlight the association between psychosocial skills at age 12 and educational progression through adolescence (to age 19), analysing Young Lives quantitative survey data of Older Cohort children and longitudinal qualitative data collected between 2007 and 2014 in undivided Andhra Pradesh, India.